Improved adulticidal activity against Aedes aegypti (L.) and Aedes albopictus (Skuse) from synergy between Cinnamomum spp. essential oils - Jirapon Aungtikun; Mayura Soonwera (Scientific Reports, 2021)
between 0.7 and 2.1 min. This combination was more toxic to both mosquito species than 1% w/v cypermethrin. These findings demonstrate that cinnamaldehyde and synergistic combinations of C. verum + C. cassia EOs and C. cassia + C. loureiroi EOs have a high insecticidal efficacy against Aedes populations.
Keywords: Insect Pest Control Strategies; Mosquito-borne diseases and control; Moringa oleifera research and applications